CD19+CD24hiCD38hi B Cells Are Expanded in Juvenile Dermatomyositis and Exhibit a Pro-Inflammatory Phenotype After Activation Through Toll-Like Receptor 7 and Interferon-α - Piper, Christopher J. M.; Wilkinson, Meredyth G. Ll.; Deakin, Claire T.; Otto, Georg W.; Dowle, Stefanie; Duurland, Chantal L.; Adams, Stuart; Marasco, Emiliano; Rosser, Elizabeth C.; Radziszewska, Anna; Carsetti, Rita; Ioannou, Yiannis; et al. (Frontiers in Immunology, 2018)
Juvenile dermatomyositis (JDM) is a rare form of childhood autoimmune myositis that presents with proximal muscle weakness and skin rash. B cells are strongly implicated in the pathogenesis of the disease, but the underlying mechanisms are unknown. Therefore, the main objective of our study was to investigate mechanisms driving B cell lymphocytosis and define pathological features of B cells in Juvenile Dermatomyositis (JDM) patients. Patients were recruited through the UK JDM Cohort and Biomarker study. Peripheral blood B cell subpopulations were immunophenotyped by flow cytometry. The results identified that immature transitional B cells were significantly expanded in active JDM, actively dividing, and correlated positively with disease activity. Protein and RNAseq analysis revealed high IFNand TLR7-pathway signatures pre-treatment. Stimulation of B cells through TLR7/8 promoted both IL-10 and IL-6 production in controls, but failed to induce IL-10 in JDM patient cells. Interrogation of the CD40-CD40L pathway (known to induce B cell IL-10 and IL-6) revealed similar expression of IL-10 and IL-6 in B cells cultured with CD40L from both JDM patients and controls. In conclusion, JDM patients with active disease have a significantly expanded immature transitional B cell population which correlated with the type I IFN signature. Activation through TLR7 and IFN may drive the expansion of immature transitional B cells in JDM and skew the cells towards a pro-inflammatory phenotype.